A facile method for the synthesis of free-standing pillar[5]arene-based two-dimensional covalent organic monolayers in solution. Issue 2 (1st February 2020) - Qiang, Hui; Hu, Wei-Bo; Chen, Tao; Liu, Yahu A.; Jia, Xue-Shun; Jiang, Biao; Wen, Ke
ABSTRACT: This report describes a facile method by which, without using any surface-assisted growth or pre-organisation, free-standing two-dimensional (2D) covalent organic monolayers (COMs ) were synthesised through condensation reactions of planar tri-aldehydes with A1/A2-diamino-substituted pillar[5]arene (DAP5 ). In the as-formed monolayers (DAP5-COM-1 and DAP5-COM-2 ), the tubular pentagonal pillar[5]arene units positioned out of the 2D polymer planes suppress efficiently the interlayer π-π stacking interactions. Both DAP5-COM-1 a nd DAP5-COM-2 can be transferred onto solid surfaces for further characterisation and were found to possess unusual fluorescence up-conversion property. Graphical Abstract: